The effect of oral hygiene on the caries prevalence among schoolchildren in Foča - Davidović Bojana; Ivanović Mirjana; Janković Svjetlana; Lečić Jelena (Serbian Medical Society - Dental Section, Belgrade, 2014)
Introduction. Caries and periodontal disease are the most common diseases afflicting oral tissues. Insufficient knowledge of the causes of these diseases leads to inappropriate behavior of patients towards their own oral health. The aim of this study was to determine the level of oral hygiene and its effect on the prevalence of dental caries in schoolchildren in Foča. Material and Methods. The study included 239 schoolchildren, 12 years old of both genders, attending four elementary schools in Foča. To assess their oral health methodology and criteria of the World Health Organization were used. Carious teeth were recorded and oral hygiene evaluated in accordance with Oral Hygiene Index. A questionnaire was used to obtain information about oral hygiene habits, reasons for dental visits as well as the number of dental visits. Results. The average number of affected teeth in the analyzed population was 5.43 and the average value of Oral Hygiene Index was 0.93. Good oral hygiene was noticed in 75% of respondents. Most respondents had at least one dental visit. Toothache was the most common reason for dental visit while the distance from clinics and fear of intervention were the most common reasons for not visiting dentist. Conclusion. In this part of Podrinje children had an average of more than five carious permanent teeth. Examined children from rural areas had poorer oral health, as well as lower number of visits to the health facilities compared to their peers in urban areas. Given that the most of examined children (75%) had good oral hygiene, other factors that led to significant number of carious teeth must be determined.